Three-dimensional batted ball in baseball: effect of ball spin on the flight distance - Nakashima, H.; Horiuchi, G.; Sakurai, S. (Sports Engineering, 2018)
In this study, three-dimensional baseball kinematics are described including spin characteristics batted toward the left field (same field), center field, and right field (opposite field) in baseball. The study also discusses the effects of these kinematics on the flight distance. Six collegiate male baseball players performed free-batting and were instructed to hit the ball as far as possible. The balls just before, at, and after bat-ball impact were recorded with three high-speed video cameras. Eighty-one trials (same field: 25 trials, center field: 30 trials, and opposite field: 26 trials) were analyzed, and the ball kinematics among the three hitting directions were compared. Although there were no significant differences in the initial velocities and launch angles along the vertical plane of batted balls for the three hitting directions, the flight distance for the opposite field was significantly shorter than that for the other fields. The magnitude of the side spin components for the opposite field was significantly greater than that for the other fields. We conjecture that the balls batted toward the opposite field experienced a larger Magnus force along the horizontal direction; moreover, the trajectories were relatively more curved than in the cases towards the other fields. Therefore, a straight-line distance to the batted ball landing point in the opposite field tended to be shorter despite the similar initial velocity and launch angle. The results demonstrated that the spin characteristics, especially the side spin component, were different for different batting directions, and indicated that these characteristics affected the ball trajectory and flight distance.